Acute mitogen‐activated protein kinase 1/2 inhibition improves functional recovery and vascular changes after ischaemic stroke in rat‐monitored by 9.4 T magnetic resonance imaging. (12th November 2017) - Mostajeran, M.; Wetterling, F.; W. Blixt, F.; Edvinsson, L.; Ansar, S.
Abstract: Aim: The aim was to evaluate the beneficial effect of early mitogen‐activated protein kinase (MEK)1/2 inhibition administered at a clinical relevant time‐point using the transient middle cerebral artery occlusion model and a dedicated rodent magnetic resonance imaging system (9.4T) to monitor cerebrovascular changes non‐invasively for 2 weeks. Method: Transient middle cerebral artery occlusion was induced in male rats for two hours followed by reperfusion. The specific MEK1/2 inhibitor U0126 was administered ip at 6 and 24 hours post‐reperfusion. Neurological functions were evaluated by 6‐ and 28‐point tests. 9.4 T magnetic resonance imaging was used to monitor morphological infarct changes at day 2, 8 and 14 after stroke and to evaluate cerebral perfusion at day 14. Immunohistochemistry evaluation of Ki67 was performed 14 days post‐stroke. Results: U0126 improved long‐term behavioural outcome and significantly reduced infarct size. In addition, cerebral perfusion in U0126‐treated animals was improved compared to the vehicle group. Immunohistochemistry showed a significant increase in Ki67 + cells in U0126‐treated animals compared to the vehicle group. Conclusion: Early MEK1/2 inhibition improves long‐term functional outcome, promotes recovery processes after stroke and most importantly provides a realistic time window for therapy.